Literasi Keuangan, Pendapatan dan Manajemen Pengelolaan Keuangan Terhadap Kinerja Keuangan UMKM di Kelurahan Ngagel Rejo Kota Surabaya - Nabila Fitri Indah Kurniawati; Munari Munari (Journal of Management and Bussines (JOMB), 2023)
The purpose of this study is to test and prove the effect of financial literacy, income, and financial management on the financial performance of MSMEs in the Ngagel Rejo Village, Surabaya City. The research method uses quantitative research. The results of this study indicate that: a) Financial Literacy on MSME Financial Performance has a significant P-Value of 0.029; b) Income on MSME Financial Performance has a significant P-Value of 0.000; c) Management of Financial Management on MSME Financial Performance has a significant P-Value of 0.429. In conclusion, financial literacy and income have a positive and significant effect on MSME financial performance, while financial management does not have a positive effect on MSME financial performance. Keywords: Financial Literacy, Income, Finance, MSMEs